Undone science and counter-expertise: fighting for justice in an Argentine community contaminated by pesticides - Arancibia, Florencia; Campos Motta, Renata (Science as culture, 2019)
STS and social movement scholars have shown the importance of ‘getting undone science done’ to advance the goals of social movements fighting environmental health injustice. The production and mobilization of counter-expertise, meaning the reliance on expertise, broadly construed, to contest regulatory decisions based on scientific knowledge, must be further analyzed by differentiating among types of expertise and strategies to mobilize them. In social mobilization against the unrestricted use of pesticides in Argentina, the affected community in Ituzaingó Anexo developed three types of expertise. The community first drew upon its own local knowledge of cases of illness and, as lay people, produced the first epidemiological map of this area. Then, they enrolled scientists and NGOs as allies to jointly learn about pesticide contamination as an explanation for illness. The enlisted scientists produced new knowledge by conducting environmental and epidemiological studies. Finally, sympathetic public health authorities, legal experts, and a district attorney designed a successful legal strategy to stop fumigations in that area and enforce local regulations. The case confirms the importance of producing undone science, and shows that its effectiveness can be explained by intertwined strategies deployed by a triad of lay/local, scientific, and legal experts to overcome the expertise barrier.